Reasons for revision are associated with rerevised total knee arthroplasties: an analysis of 8,978 index revisions in the Dutch Arthroplasty Register - Belt, Maartje; Hannink, Gerjon; Smolders, José; Spooren, Anneke Spekenbrink-; Schreurs, Berend W; Smulders, Katrijn (Acta Orthopaedica, 2021)
Background and purpose — From previous studies, we know that clinical outcomes of revision total knee arthro- plasty (rTKA) differ among reasons for revision. Whether the prevalence of repeat rTKAs is different depending on the reason for index rTKA is unclear. Therefore, we (1) com- pared the repeat revision rates between the different reasons for index rTKA, and (2) evaluated whether the reason for repeat rTKA was the same as the reason for the index revi- sion. Patients and methods — Patients (n = 8,978) who underwent an index rTKA between 2010 and 2018 as regis- tered in the Dutch Arthroplasty Register were included. Rea- sons for revision, as reported by the surgeon, were catego- rized as: infection, loosening, malposition, instability, stiff- ness, patellar problems, and other. Competing risk analyses were performed to determine the cumulative repeat revision rates after an index rTKA for each reason for revision. Results — Overall, the cumulative repeat revision rate was 19% within 8 years after index rTKA. Patients revised for infection had the highest cumulative repeat revision rate (28%, 95% CI 25–32) within 8 years after index rTKA. The recurrence of the reason was more common than other rea- sons after index rTKA for infection (18%), instability (8%), stiffness (7%), and loosening (5%). Interpretation — Poorest outcomes were found for rTKA for infection: over 1 out of 4 infection rTKAs required another surgical intervention, mostly due to infection. Recur- rence of other reasons for revision (instability, stiffness, and loosening) was also considerable. Our findings also empha- size the importance of a clear diagnosis before doing rTKA to avert second revision surgeries.